Larval dispersal and recruitment of benthic invertebrates in the Arctic Ocean. (April 2022) - Meyer-Kaiser, Kirstin S.; Schrage, Kharis R.; von Appen, Wilken-Jon; Hoppmann, Mario; Lochthofen, Normen; Sundfjord, Arild; Soltwedel, Thomas
Highlights: We combined observations from larval traps, fouling panels, and opportunistic sampling of biofouling on oceanographic moorings to study larval dispersal in the Fram Strait and on the north Svalbard continental slope. Species composition was significantly different between samplers exposed to Atlantic Water in the West Spitsbergen Current and samplers exposed to Arctic Water in the East Greenland Current and near the seafloor. Most of the collected individuals belonged to species with long-duration planktotrophic larvae. We also observed reproduction via a medusa stage in the hydrozoans Rhizoragium roseum and Stegopoma plicatile . The WSC is an important vector for dispersal of benthic invertebrates into the central Arctic Ocean. Abstract: Larval dispersal is a fundamental process responsible for colonization and connectivity of benthic invertebrate populations. It is difficult to study larval dispersal in polar environments because weather and climate conditions restrict sample collection to certain seasons. In this study, we leveraged oceanographic moorings as long-term scientific platforms for collecting larvae and recruits of benthic invertebrate species in the Fram Strait and along the continental slope north of Svalbard in 2017–2021. Larval traps and fouling panels were deployed at various depths on 15 moorings at 8 locations, and additional specimens of biofouling were obtained opportunistically from moored instruments. Our results showed a significant difference in species composition between samples collected in Atlantic Water in the West Spitsbergen Current (WSC) and samples collected in Arctic Water near the seafloor and in the East Greenland Current (EGC) in the western part of the Fram Strait. There was also a stark difference between Atlantic Water species in the Fram Strait and on the north Svalbard slope. Most specimens collected in the WSC belonged to species with long-duration planktotrophic larvae, such as the ubiquitous bivalve Hiatella arctica, the bryozoan Alcyonidium mamillatum, and two nudibranchs. Samplers exposed primarily to Arctic water at their given depth and location were dominated by hydrozoans. We observed medusae budding off of the hydroids Stegopoma plicatile and Rhizoragium roseum . Our study demonstrates that the WSC is an important vector for larval dispersal into the central Arctic Ocean. Integration of biological samplers on oceanographic moorings holds great promise for monitoring efforts as climate change progresses, especially in environments where research is challenging and seasonally limited, such as the Arctic.